Free opposition vs free appointment to the Education Inspectorate: PART I. From the “Veedores” to the 1978 Constitution - Tébar Cuesta, Fernando; Gregorio Arroyo, Alicia (Avances en Supervisión Educativa, 2023)
The history of the Inspectorate of Education is an attractive field in which curious minds always have something to reflect on and learn from. This article is a triangle in which the author links the reader to the history of the Inspectorate. It brings the vicissitudes of an administrative corps (basically dedicated to administrative tasks although it draws on the teaching corps) to those interested in a concise way, trying to answer some questions that are relevant to the Inspectorate.The aim of this work is to investigate the realities, causes and procedures in the different forms of access and successive competitive examinations for the Education Inspectorate. Points of view have been put forward on each access and, as far as possible, their social and political justification. If the early years of the 19th century are still far away, we are fortunate to have the work of numerous historians who are also Education Inspectors.All of this, together with the invaluable help of the BOE, the Gaceta and the bulletins of the autonomous communities, has made it possible to present this work, which shows the continuous effort of the Inspectorate to achieve a margin of confidence in the institution itself, demanding conditions degree, seniority in the corps of origin or the improvement in the composition of the tribunals, which would provide each call with seriousness and solvency.Given the long time period, the study is divided into two parts, the first covers the historical period from the creation of the Corps to the Spanish Constitution of 1978, the second continues from that moment to the present.
Keywords: Public examination; free appointment; Education Inspectorate; access systems; research; recruitment process; access examinations; conditions; courts; merit and ability